2014
DOI: 10.1080/10508422.2014.950269
|View full text |Cite
|
Sign up to set email alerts
|

Peruvian Female Sex Workers’ Ethical Perspectives on Their Participation in an HPV Vaccine Clinical Trial

Abstract: This study examined female sex workers’ evaluation of ethically relevant experiences of participating in an HPV4 vaccine clinical trial conducted in Lima, Peru (the Sunflower Study). The Sunflower Study provided all participants with HPV testing, treatment for those testing positive, and access to the vaccine for all testing negative. Themes that emerged from content analysis of interviews with 16 former participants included the importance of respectful treatment and access to healthcare not otherwise availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 38 publications
(55 reference statements)
1
16
1
Order By: Relevance
“…Participants identified structural factors such as stigma associated with both sex work and HIV, as well as manager control, as barriers to research engagement, which relate to the broader context of discrimination and human rights violations experienced by sex workers in Central America (Goldenberg, Strathdee, Perez-Rosales, & Sued, 2012; Infante, Aggleton, & Pridmore, 2009; Rocha- Jiménez et al, Under review) and other settings (Lazarus et al, 2012; Scambler & Paoli, 2008; Shannon et al, 2014; Brown, Davtyan, & Fisher, This issue). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants identified structural factors such as stigma associated with both sex work and HIV, as well as manager control, as barriers to research engagement, which relate to the broader context of discrimination and human rights violations experienced by sex workers in Central America (Goldenberg, Strathdee, Perez-Rosales, & Sued, 2012; Infante, Aggleton, & Pridmore, 2009; Rocha- Jiménez et al, Under review) and other settings (Lazarus et al, 2012; Scambler & Paoli, 2008; Shannon et al, 2014; Brown, Davtyan, & Fisher, This issue). …”
Section: Discussionmentioning
confidence: 99%
“…Studies with sex workers in Peru (Brown et al, This issue), India (Reed et al, 2014) and the Philippines (Urada & Simmons, 2014) have identified stigma and a lack of respect for persons as concerns associated with HIV and sexual health research. This evidence indicates the need for researchers to enhance efforts to reduce stigma and its impacts on research, for example, by hiring staff from community-based organizations that adopt a non-judgmental approach; training team members to demonstrate respect and reciprocity; hiring current or former FSWs to lead, conduct and/or assist with research; and to support broader efforts of sex workers to organize and advocate for respectful treatment and de-stigmatization of their work.…”
Section: Discussionmentioning
confidence: 99%
“…The new FDA approved Oraquick rapid HIV home testing kits, available without prescription, provides an opportunity for overcoming barriers to HIV testing. Prior to the intervention, survey items illuminated barriers to HIV testing including misconceptions regarding the relationship of HIV to AIDS, fear of getting recognized at the HIV testing sites, concerns about the confidentiality of results, and as also reported by Brown et al (2015/this issue) trepidation about learning they were HIV positive accompanied by fear of losing a partner or spouse if they tested positive. The educational intervention led to a reduction in HIV misconceptions as well as a reduction in endorsement of items reflecting stigmatization of individuals with HIV.…”
Section: An Overview Of the Special Issue Contributionsmentioning
confidence: 99%
“…[ 38 41 ] Previously identified ethical issues in global health research with marginalized and highly vulnerable populations, such as sex workers and people who use drugs, include: concerns regarding disclosure of illicit and often stigmatizing behaviors; the potential for exploitation and lack of respect for participants by research teams; inadequate community engagement; stress and burnout among front-line research staff; and disappointment when the research fails to improve policies or working conditions. [ 39 , 44 59 ] Applicability of research to the eventual implementation of interventions and programmes serving this population may be of particular concern for marginalized populations recruited for epidemiological studies. There is a paucity of work on these and other ethical concerns in HIV research with migrant women, including the unique challenges for front-line research staff working with highly vulnerable and transient populations[ 39 , 53 , 58 ] and the potential for research to unintentionally fuel (mis)perceptions of migrant sex workers as “vectors of disease” or as sex trafficking victims[ 1 , 38 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%